The hooker and the hermit eaudiobook - Cosway, L. H. (Tantor Audio, 2015)
Annie Catrel, social media expert extraordinaire at Davidson & Croft Media and clandestine celebrity blogger, can make anyone shine in the court of public opinion. She is the Socialmedialite, anonymous creator of New York's Finest and the internet's darling. Virtual reality is Annie's forte, but actual reality? Not so much. Ronan Fitzpatrick, AKA the best hooker the world of rugby has seen in decades, despises the media-social or otherwise. The press has spun a web of lies depicting him as rugby's wild and reckless bad boy. Suspended from his team, Ronan has come to Manhattan to escape the drama. When Ronan is sent to Davidson & Croft Media to reshape his public image, he never expects to cross paths with shy but beautiful Annie, nor does he expect his fierce attraction to her. What lengths will Annie take to keep her virtual identity concealed? And what happens when Ronan discovers who she really is?Contains mature themes.